Potency of Endophyte Bacterium Isolated from Shorea selanica on Producing IAA Hormone and Supporting the Growth of Soybean - Widowati, Tiwit; Nuriyanah, Nuriyanah; Sukiman, Harmastini (BRIN, 2013)
Growth of soybean plants was supported by the presence of nitrogen fixing bacteria. Besides nitrogen, other elements such as phosphate, potassium and growth hormones are also required. Endophytic bacteria associated with Shorea selanica were isolated and tested for their ability to produce indole acetic acid (IAA) hormone and exhibit stress tolerance. Colorimetric analysis showed that isolate SSBt2 produced the highest IAA (43.01 μg/ml) in culture supplemented with L-tryptophan. Isolate SSBt2 grew well in the some stress tests, except on heat and oxidative stress. The highest IAA producing strain was selected for determining its capability and compatibility to support the growth of soybean plants in glass house experiment. The results indicated that the endophytic bacteria isolated from S. selanica are compatible to support the growth of soybean. SSBt2 was identified as Enterobacter hormaechei based on 16S rRNA gene analysis.